Determination and Study of Soil Using Richard's Law - Shamal, Shekeb; Rasouli, Hafizullah (Journal of Natural Sciences – Kabul University, 2023)
The determination of soil porosity is a crucial aspect of soil science, particularly in geology, where it plays a significant role in groundwater movement. Generally, soil porosity is directly related to the particle size: larger particles result in larger pores but fewer porosities, while smaller particles lead to more porosities but lower permeability. In cases where particles are small and non-homogeneous, the permeability of the soil decreases. This research aims to investigate the relationship between soil porosity and permeability, using Richard's Law, and is relevant to geology, engineering, and agriculture.